ROLA WIEDZY SPECJALISTYCZNEJ W USTNEJ KOMUNIKACJI SPECJALISTYCZNEJ NA ZAJĘCIACH JĘZYKA EKONOMICZNEGO - Cholewa, Justyna (Neofilolog, 2020)
Verbal communication for specific purposes during language classes invariably involves the decision making process. Decisions primarily concern specialized content and linguistic expressions. The participants in the communication, i.e. teachers and learners, must there-fore have an appropriate level of language competence and expertise. This specialist knowledge, defined as specific knowledge of a professional area and activities related to it, includes both substantial knowledge of the field, knowledge of terminology and discourse structures. Expertise plays an essential role in every aspect of teaching a foreign language for business purposes, as oral communication skills are developed on the basis of specialist knowledge. Broadening specialist knowledge is hence both means and purpose. Deficiencies in specialist knowledge can be seen in the performance of communication tasks when it hinders the ability to reach an agreement. The aim of this article is to analyse the role of expertise in oral communication for specific purposes in business language classes with reference to the author's own research.